A new species of Apocellus Erichson, 1839 (Coleoptera: Staphylinidae) from Argentina with ecological notes - Chani-Posse, Mariana; Scheibler, Erica E. (Zootaxa, 2013)
Apocellus andinus sp. nov. from Argentina is described and illustrated, detailed information on its ecology is provided, and a key to species of Apocellus from southwestern South America is given. This species was collected in riparian areas of a mountain dam at 1355 m elevation, and it was found in an unstable wetland environment in association with species tolerant to human perturbations. Lectotypes are designated for Apocellus argentinus Bernhauer, 1908 and Apocellus opacus Bernhauer, 1908.